Seismic Analysis of a Viscoelastic Damping Isolator - Bo-Wun Huang; Jao-Hwa Kuang; Jung-Ge Tseng; Jyun-Cin Wang; Yu-Xian Qiu (Advances in Materials Science and Engineering)
Seismic prevention issues are discussed much more seriously around the world after Fukushima earthquake, Japan, April 2011, especially for those countries which are near the earthquake zone. Approximately 1.8×1012 kilograms of explosive energy will be released from a magnitude 9 earthquake. It destroys most of the unprotected infrastructure within several tens of miles in diameter from the epicenter. People can feel the earthquake even if living hundreds of miles away. This study is a seismic simulation analysis for an innovated and improved design of viscoelastic damping isolator, which can be more effectively applied to earthquake prevention and damage reduction of high-rise buildings, roads, bridges, power generation facilities, and so forth, from earthquake disaster. Solidworks graphic software is used to draw the 3D geometric model of the viscoelastic isolator. The dynamic behavior of the viscoelastic isolator through shock impact of specific earthquake loading, recorded by a seismometer, is obtained via ANSYS finite element package. The amplitude of the isolator is quickly reduced by the viscoelastic material in the device and is shown in a time response diagram. The result of this analysis can be a crucial reference when improving the design of a seismic isolator.